Assessment of ship-block stacking status based on images obtained from drone and geographic information system data - Young-Soo Han; Kyungho Lee; Byeongwook Nam; Yang Ouk Kim; Youngsu Kim; Hyeon-Bin Yeo (International Journal of Naval Architecture and Ocean Engineering)
Ships are constructed using the shipbuilding method, which involves several blocks. Every block produced in each unit process features a different production speed depending on the block shape, number of members used, and process complexity. Consequently, the blocks produced in one process is stored in the stockyard for the next process operation. As the number of blocks stacked in the stockyard increases, the movement of the blocks and that of their transporters increase, thus resulting in an increase in operating costs. Hence, we propose a method for monitoring the block storage status based on drone images and shipyard Geographic Information System (GIS) information to support the efficient use of block stockyards. Shipyard GIS information is mapped onto the image acquired from the drone, and the area of the stacked block is detected in the image. The block storage area and storage load factor of the stockyard are calculated using the saved block areas and shipyard GIS information. By evaluating shipyard stockyards, we confirmed the possibility of monitoring the status of shipyard block storage based on drone images and GIS information.